Insomnia dalam Psikologi dan Pandangan Islam tentang Ketenangan Jiwa - Rahmatullah, Azam Syukur; Syafii, Muhammad Hisyam (Lembaga Yasin AlSys, 2025)
This study discusses the phenomenon of insomnia as a disorder of sleep quality that is increasing, especially among adolescents and young adults. Insomnia not only has an impact on an individual's health but can also trigger social problems, such as increased negative behavior due to failure to control oneself. This study aims to understand the psychological factors that contribute to insomnia and how the concept of peace of mind in Islam can be a solution in overcoming it. The research method used is a qualitative descriptive approach with field study studies through observations, observations, and interviews which are then strengthened by literature study and data analysis from various sources of psychology and Islamic teachings. The results of the study show that stress, anxiety, and an unhealthy lifestyle are the main factors that trigger insomnia. From an Islamic perspective, worship practices such as dhikr, tahajud prayers, and maintaining spiritual balance can have a calming effect that helps with sleep disorders. Likewise, from most people in Indonesia, especially in Jogyakarta and Central Java, that the number of insomnia is due to excessive stress, both from problems, pressure obligations and also lack of regular sleep. The impact is that daily life becomes more difficult or unpleasant. Therefore, this study emphasizes that Islamic psychological and spiritual approaches can be an effective solution in managing and reducing insomnia experienced by the community by convincing themselves and activities in the environment.